Pengaruh Kualitas Produk, Harga dan Kualitas Pelayanan terhadap BrandSwitching Laptop Merek Axioo pada Mahasiswa Universitas Negeri Padang - Dwi Fitrian Armazura; Susi Evanita; Abel Tasman (Universitas Negeri Padang, 2019)
Purpose - This study aims to analyze and prove: (1) the influence of product quality on the brand switching Axioo brand laptop (2) the effect of prices on the brand switching Axioo brand laptop (3) the influence of services on the brand switchingAxioo brand laptop. This type of research is causative research. Methodology -The population in this study were students from Universitas Negeri Padang who used Axioo brand laptops. The total sample of this study was 97 people who were taken using a purposive sampling method because the unknown population used a questionnaire. Finding - The results of this study indicate that (1) Product quality has a negative and significant effect on the brand switching Axioo brand laptop. (2) Price has a positive and significant effect on Axioo Brand Switching laptops (3) Service Quality has a negative and not significant effect on the Switching Brand laptop brand. Keywords: Product Quality, Price, Service Quality, Brand Switching